Chapter Fears and hopes: Chinese university students in Italy during the first wave of Covid-19 - XU, HAO (Firenze University Press, 2023)
In recent years, Chinese students have enjoyed a prominent presence in the Italian higher education system. A recent survey conducted by Uni-Italia shows that Chinese students account for 24% of non-EU students in Italian universities. When the novel coronavirus (COVID-19) erupted in Italy at the beginning of 2020, panic spread quickly through social media; numerous fears, generated by the tide of information available online, permeated the Chinese university student community in Italy. This chapter first analyses the problems encountered by Chinese university students in Italy during the COVID-19 pandemic, and then introduces the artistic and cultural response from within that same community. Such forms of creative response also shine light, more generally, on a growing Anti-Asian sentiment in Italy. Despite the enormous challenges posed by COVID-19, Chinese university students in Italy have developed a mode of communication that builds bridges between different cultures— quite different from “mass media” or “major news outlets”—because it is personal, honest, and intimate.